Neonatal Milk Fat Globule Membrane Supplementation During Breastfeeding Ameliorates the Deleterious Effects of Maternal High-Fat Diet on Metabolism and Modulates Gut Microbiota in Adult Mice Offspring in a Sex-Specific Way - Ye, Lin; Zhang, Qianren; Xin, Fengzhi; Cao, Baige; Qian, Linxi; Dong, Yan (Frontiers in Cellular and Infection Microbiology, 2021)
Exposure to adverse events in early life increases the risk of chronic metabolic disease in adulthood. The objective of this study was to determine the significance of milk fat globule membrane (MFGM)-mediated alterations in the gut microbiome to the metabolic health of offspring in the long-term. Female C57BL/6 mice were fed either a high-fat diet (HFD) or a control diet for 3 weeks before pregnancy and throughout pregnancy and lactation. During lactation, pups from the HFD group were breast-fed with or without 1,000 mg/kg BW/day MFGM supplementation (HFD and HFD-MS group, respectively). After weaning, the offspring in each group were divided into male and female subgroups. The weaned mice were then shifted to a control diet for 8 weeks. At the eleventh week, stool samples were collected for 16S rRNA gene sequencing. Serum biochemical parameters were analyzed, and intraperitoneal glucose and insulin tolerance tests were performed. Neonatal supplementation with MFGM ameliorated metabolic disorder and improved glucose tolerance in offspring exposed to maternal HFD in a sex-specific manner. Furthermore, maternal HFD induced gut microbiota perturbation in offspring in adulthood. Neonatal MFGM supplementation significantly enriched g-Parabacteroides, g-Bifidobacterium, g-Faecalibaculum, and g-Lactobacillus in male offspring exposed to maternal HFD, while significantly enriched g-Parabacteroides and g-Alistipes in female offspring exposed to maternal HFD. These bacteria may be associated with the favorable changes in metabolism that occur in adulthood. Sex differences in the changes of metagenomic pathways related to oxidative phosphorylation, citrate cycle, electron transfer carries, and ubiquinone biosynthesis were also observed in the offspring. Maternal HFD has an adverse effect on the metabolism of offspring in later life. Neonatal MFGM supplementation could modulate the structure of gut microbiota communities and may have long-term protective effects on lipid and glucose metabolism, but these effects are sex dimorphic.